Designating Appointing Authorities in UNCITRAL Arbitration: Wrong and Imperfect Designations - Stanivuković, Maja (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
The parties have a right to designate an appointing authority that will select and appoint the arbitrators in case the parties cannot agree on their appointment, and decide on challenges to arbitrators in an international arbitration. However, if they lack experience, knowledge or are simply not careful enough, they can make wrong designations which result in appointing authorities that are not neutral. Sometimes, also, errors in drafting clauses that designate the appointing authority lead to imperfections and incoherences, which may frustrate the parties’ choice of the appointing authority and adversely affect the entire arbitration. In this paper we shall examine the operation of arbitration clauses designating appointing authorities on two relatively recent examples from the combined UNCITRAL-ICC practice, with the aim to identify potential problems arising from wrong and imperfect designations, and suggest solutions.